Metacognitions in patients with chronic obstructive pulmonary disease: a psychometric study of the metacognitions questionnaire-30 - Dammen, Toril; Papageorgiou, Costas; Lindstrøm, Jonas Christoffer; Einvik, Gunnar (Frontiers in Psychology, 2023)
The metacognitions questionnaire-30 (MCQ-30) was developed for the assessment of metacognitive beliefs and processes that are central components of the metacognitive model of emotional disorders. Anxiety and depression commonly occur in patients with chronic obstructive pulmonary disease (COPD). Testing such a model for anxiety and depression in patients with COPD is warranted. However, the psychometric properties of the MCQ-30 in COPD patients are unknown. Therefore, in this study we aimed to examine these properties in COPD patients. The MCQ-30 was administered to 203 COPD patients referred to a rehabilitation unit in respiratory medicine. Confirmatory factor analysis (CFA) was used to test the five-factor as well as the bi-factor models of MCQ-30. Exploratory factor analyses were also performed. Both models did not meet the criteria for an acceptable fit on Comparative Fit Index (CFI) of 0.810 and 0.858 vs criterion of > 0.9, but the Root Mean Square Error of Approximation (RMSEA) criterion < 0.08 was acceptable for both models with RMSEA = 0.074 and 0.066, respectively. The factors were mostly moderately correlated (0.41-0.58) with acceptable reliability coefficients (0.73-0.87). The exploratory factor analysis identified three of the five factors originally described in the five-factor model of the MCQ-30. These data show that the factor structure of the MCQ-30 appears to differ from that of the original instrument in COPD patients and further studies are needed to confirm its validity and reliability in this patient group.